Ukraine’s Balance Policy between European Union and Russia - Ozan Sabri Tuncer Tuncer; Fatma Nur Erkut (Acta Politica Polonica, 2022)
Having declared independence in 1991, after the dissolution of the Soviet Union, Ukraine gained strategic importance in terms of its geographical location. It is regarded a “buffer zone” for both the European Union (EU) and Russia. There is a division within the country into the pro-Western and pro-Russian options. Ukraine’s aspiration for the UE membership has faced Russia’s objection since time immemorial. In the past, Ukraine preferred to pursue a balance policy between Russia and the EU. Ukraine’s attempt to approach the West with the Orange Revolution, its inclusion in the European Neighbourhood Policy, its participation in the Eastern Partnership program were perceived as a threat by Russia. The Ukrainian crisis, in particular, brought these two countries face to face. This crisis also deeply affected both the EU’s energy policy and its relations with Russia. After all the developments that followed, the issue of Ukraine’s membership in the EU remains uncertain.